FRI0574 One-Year Tuberculosis Risk in Rheumatoid Arthritis Patients Initiating Tumor Necrosis Factor-α Inhibitor from 2003 To 2011 in Taiwan: A Nationwide Population-Based Cohort Study. (15th July 2016) - Chen, H.-H.; Chen, Y.-M.; Lai, K.-L.; Lin, C.-H.; Chen, D.-Y.; Lim, C.-H.; Tsai, C.-J.
Abstract : Background: Use of tumor necrosis factor-α inhibitor (TNFi), especially monoclonal antibody, may increase the risk of tuberculosis (TB) infection in patients with rheumatoid arthritis (RA). The emergence of active TB in RA patients receiving TNF-α inhibitor showed a biphasic pattern. The strategy of latent TB infection (LTBI) screening and treatment theoretically may reduce TB reactivation, which mainly contributes to the first phase of TB emergence. In Taiwan, etanercept and adalimumab were approved for RA treatment in 2003 and 2007 respectively. Objectives: To examine the 1-year risk of TB infection in RA patients initiating TNFi therapies as compared to RA patients not treated with TNFi in Taiwan stratified by treatment initiation year (2003 to 2011). Methods: Data was collected retrospectively using the 2003–2012 claim data from the Taiwanese National Health Insurance Research Database. We enrolled all treated RA patients initiating TNFi therapy as the study cohort, and those who never received TNFi therapy as the comparison cohort from 1st January 2003 to 31st December 2011. All patients were followed up for one year after starting treatment. The diagnosis of TB was identified using ICD-9-CM and the prescription of at least 2 anti-TB drugs within 6 months of TB diagnosis made. The 1-year TB risk of TNFi users compared with non-TNFi users was shown as incident rate rations (IRR) with 95% confidence intervals (CI) and adjusted hazard ratios (aHRs) using Cox's regression analysis after adjustment of potential confounders including age, sex, disease duration, TB history, comorbidities and concomitant medications, further stratified by the year of treatment initiation. Results: A total of 46, 668 RA patients were included; 40, 678 (87.2%) in non-TNFi and 5, 990 (12.8%) in TNFi group. A total of 163 1-year TB events were reported; 136 in non-TNFi group and 27 in TNFi group with 1-year TB incidence rate of 369 and 504 per 100, 000 patient-years respectively. The 1-year TB risk was higher in TNFi users compared with non-TNFi users (IRR, 1.37; 95% CI, 0.71–2.07; aHR, 7.27; 95% CI, 3.65- 14.48). As shown in Figure 1, the IRR of TB within one year in adalimumab users compared with non-TNFi users peaked in 2008 (IRR, 4.57) and was lowest in the 2011 group (IRR, 0.49). Other significant risk factors of 1-year TB infection included age≥65 years (aHR, 1.52, 95% CI, 1.09–2.10), male (aHR, 1.81, 95% CI, 1.31–2.51) and prior TB infection (aHR, 29.28; 95% CI, 18.62–46.05). Conclusions: The 1-year risk of TB in RA patients initiating TNFi was significantly higher than non-TNFi users. During 2008–2011, the 1-year TB IRR in adalimumab users compared with non-TNFi users dropped from 4.57 to 0.49, which might be explained by increasing physician/patient awareness with LTBI screening and treatment. References: Chen DY, Shen GH, Chen YM, Chen HH, Hsieh CW, Lan JL. Biphasic emergence of active tuberculosis in rheumatoid arthritis patients receiving TNFalpha inhibitors: the utility of IFNgamma assay. Annals of the rheumatic diseases. 2012;71(2):231–7. Disclosure of Interest: H.-H. Chen Grant/research support from: AbbVie Biopharmaceuticals GmbH Taiwan Branch, Y.-M. Chen: None declared, K.-L. Lai: None declared, C.-H. Lin: None declared, D.-Y. Chen: None declared, C.-H. Lim: None declared, C.-J. Tsai: None declared